Meta-analytic review of servant leadership and team member exchange (TMX) theory - Nur Aisyah; Retno Purwani Setyaningrum; Endah Budiarti; Ida Bagus Cempena; Suhardi Suhardi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Research on the relationship between Servant Leadership (SL) and Team Member Exchange (TMX) has been carried out. At the same time, the basis for this relationship and the mechanism and conditions are still minimal and poorly understood by many people. The methodology that we use in this study is a meta-analysis method by searching for empirical research with the help of Google and also Researchgate through the keyword Leadership that was selected at first. Then, sort out the discussion that focuses on Servant Leadership and Team Member Exchange (TMX) research as concepts and the relationship between variables, and then summarise them. This summary describes the importance of Servant Leadership and Team Member Exchange (TMX) mechanisms in improving Performance. By providing a nuance of understanding about how Servant Leadership (SL) and Team Member Exchange (TMX) can play a role in one's work so that they can help the company or organization in its development so that it can make decisions that are beneficial to the performance of employees and their organization. In the end, we provide some interesting views and suggestions for further research.